The Impact of Different Types of Polishing Bur on the Nanofiller Composite's Surface Roughness - Dwi Harini Endah Meidianti; Deviyanti Pratiwi; Rosalina Tjandrawinata (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Composite resin is a filling material that is similar in color to tooth enamel and can be used widely for various cases, especially for the restoration of anterior teeth. Composite resins have been modified and improved to obtain maximum restoration results, one of which is nanofiller. Nanofiller composite is known to have a high level of smoothness, but polishing remains the key to success in the final filling process. There are many types of polishing on the market, this indicates that not all dentists use the same type of tools. This study aimed to determine the effect of various types of polishing bur on the surface roughness of nanofiller.Method: The type of research conducted was an experimental laboratory. Cylindrical samples with a total of 40 samples measuring 10 mm x 2 mm were divided into 4 groups. Samples were soaked in distilled water and stored in an incubator for 24 hours at 37oC. The samples were polished using different types of bur except for the control group. Samples were tested for surface roughness using a surface roughness tester and scanning electron microscopy (SEM). Result: This study shows differences in the surface roughness of the nanofiller composite after being polished using different types of polishing burs. The results of the one-way ANOVA test indicated that there was a significant difference from the average of the four sample groups.Conclusion: Polishing burs can produce different surface roughness of nanofiller composite.